Optimizing hybrid LC–MS/MS binding conditions is critical: impact of biotransformation on quantification of trastuzumab. (16th October 2018) - Liu, Luna; Xu, Keyang; Li, Jenny; Maia, Mauricio; Mathieu, Mary; Elliott, Rebecca; Yang, Jihong; Nijem, Ihsan; Kaur, Surinder
Background: Hybrid ligand-binding (LB) LC–MS/MS protein quantitative assays involve a LB step for analyte enrichment that has less stringent requirements than the conventional LB assays.Results: Herceptin™(trastuzumab) binding to HER2 extracellular domain was evaluated using on-bead and off-bead capture formats. The two formats yielded significantly different trastuzumab concentrations in human and monkey serum pharmacokinetic samples. Biotransformations, including deamidation of asparagine and isomerization of aspartic acid near the complementarity-determining regions of trastuzumab, had a profound impact on the LB step for analyte enrichment and trastuzumab quantification.Conclusion: Quantitative measurements were profoundly impacted by LB conditions in a hybrid LB LC–MS/MS protein assay due to biotransformations. Therefore, similar to conventional LB assays, binding conditions should be carefully evaluated during assay development.